2011
DOI: 10.1177/0269215511405079
|View full text |Cite
|
Sign up to set email alerts
|

Dysarthria following stroke – the patient’s perspective on management and rehabilitation

Abstract: The quantity and nature of inconspicuous, internalized, cognitive activities people with dysarthria engage in to maximize their communicative effectiveness should be considered in evaluating the impact of dysarthria following stroke. Focusing upon externally observable characteristics alone is insufficient. Challenging, functionally relevant, patient-focused activities, materials and targets are more likely to be perceived by the patient as relevant and worthwhile and are thus more likely to ensure adherence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…For example, personal accounts suggest that speech treatment for dysarthria was the most stressful of all therapies (Cant, 1997). In another example, survey data indicate that people with Parkinson's disease reported a lack of attention to psychosocial issues, and interviews suggest that if treatment activities were not challenging and reflective of patients' interests, they were abandoned (Brady, Clark, Dickson, Paton, & Barbour, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, personal accounts suggest that speech treatment for dysarthria was the most stressful of all therapies (Cant, 1997). In another example, survey data indicate that people with Parkinson's disease reported a lack of attention to psychosocial issues, and interviews suggest that if treatment activities were not challenging and reflective of patients' interests, they were abandoned (Brady, Clark, Dickson, Paton, & Barbour, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…However, the TIA research which has been conducted has reported outcomes which, while less severe, are similar to those that result from full stroke. For example, fatigue [9, 19], cognitive dysfunction [11], dysarthria [18], and quality of life [12] have all been reported for TIA patients and mirror the experiences reported by stroke patients. The core theme of factor 2, while corroborating these research findings, also challenges the notion that TIA is transitory.…”
Section: Discussionmentioning
confidence: 99%
“…Some work has been conducted on stroke patients' experiences, but this has tended to use either established psychometric questionnaires [17], which therefore prescribe the issues to be investigated, or alternatively open-response approaches which have focused on a single element of the poststroke experience, such as dysarthria [18], or fatigue [19]. Such studies, therefore, define the area of interest and the outcomes to be measured and consequently are not a comprehensive account of the spectrum of factors that may be perceived to be pertinent by patients themselves.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its frequency, non‐progressive dysarthria management tends to receive less specific attention in the literature (Brady et al . , Dickson et al . ).…”
Section: Introductionmentioning
confidence: 99%